The Importance of Intercultural Communication in Modern Business - Bakic Miric, Natasa M.; Janković, Anita V.; Erkinovich Gaipov, Davronzhon (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
One of the main goals of modern business is the promotion of contacts between cultures, which implies the need to know and understand other cultures. In today’s globalized market, intercultural teamwork and collaboration are essential to business success. However, intercultural cooperation is not at all simple because many problems arise from the fact that communication is conditioned by knowledge of different cultures. Through Hofstede’s and Tompenaars’ models of cultural dimensions, this paper analyses the impact of culture on business intercultural communication as well as cultural differences that, although seemingly universal at first glance, actually differ greatly and thus affect the business. The rules of national culture play one of the crucial roles in creating an appropriate way of doing business. The most important thing for a businessperson is to recognize that the value system they have learned in their own culture is only part of what is called culture in the 21st century. Instead, they should focus on the differences that exist in other cultures that affect interpersonal relationships and international business, because by observing other cultures, one can learn a lot about one’s own culture. As the business world becomes globally connected more than ever, being an active listener and a culturally competent interlocutor represent a solid base for effective intercultural communication in modern business.
Keywords: business; intercultural communication; culture; dimensions of culture